Las cámaras y botones de pánico de seguridad ciudadana en el transporte público masivo en Quito, 2016 – 2018. - Corrales Barragán, Darwin Wladimir (2020)
In the present investigation entitled "The cameras and buttons of citizen security in mass public transport in Quito, in the period 2016 - 2018", develops the analysis of the implementation of the public policy of public security related to panic buttons and cameras of security in public transport in Quito within the Safe Transportation Project in relation to the control, prevention, use of technology, institutional coordination, threats and the impact of this public policy in the emergency records of the crimes of robbery, theft and harassment through citizen security indicators. Therefore, a case study was carried out in the Metropolitan District of Quito, our objective was to describe and analyze the effect and impact of the implementation of the Safe Transportation Project in the Metropolitan District of Quito, which is why it was correctly considered conduct a mixed investigation based on data from specialized primary and secondary sources, both qualitative and quantitative, of document analysis and expert interviews, with the statistical data of the emergency registry and monitoring of the operation of the cameras and citizen security buttons in the Safe Transportation Plan in mass public transportation in Quito.